2006 Conference of the International Hormesis Society: Stress Response Mechanisms: From Single Cells to Multinational Organizations - Richard J. Pech (SAGE Publishing, 2006)
Can a literal comparison be made between biological phenomena in organisms and phenomena in human organizations? The evidence provided by simplified but useful examples appears to suggest that a phenomenon simulating hormesis can and does occur in organizational contexts. Similarities between stress response behaviors of organisms and stress response behaviors in organizations are discussed. Cellular stress response mechanisms stimulate and repair, as well as defend the organism against further attacks. Organizational hormesis describes actions that stimulate the organization by increasing its focus and protecting it against future attacks. The common aim for the organism as well as the organization is to increase the probability of survival. The following describes examples of organizational survival that demonstrate a number of hormetic parallels between organisms and organisations.